A comparison of distal femoral locking plates for distal femur fractures: long working length versus short working length - Faaiz Ali Shah; Mian Amjad Ali; Naeemullah; Waqar Hassan; Syed Imran Bukhari (Journal of the Pakistan Medical Association, 2022)
Objective: To compare long working length distal femoral locking plates with short working length for treating extra-articular distal femur fractures in terms of union and implant failure. Method: The randomised controlled trial was conducted at the Lady Reading Hospital, Peshawar, Pakistan, from April 28, 2018, to March 10, 2021, and comprised all adult patients of either gender with extra-articular distal femur fractures who were randomised into two groups. Group A was exposed to long working length, while group B had short working length. Patients in both the groups were followed up regularly for one year for the assessment of fracture union and implant failure. Data was analysed using SPSS 22. Results: Group Of the 61 patients, 30(49.2%) were in group A; 24(80%) males and 6(20%) females with overall mean age 37.9±9.6 years. The remaining 31(50.8%) were in group B; 26(83.8%) males and 5(16.1%) females with overall mean age 37.2±1 years. The mean working length in group A was 75±5mm and in group B it was 35±9mm. In group A 28(93.3%) fractures healed, while in group B 19(61.2%) fractures achieved union (p=0.01). Non-union was noted in 2(6.6%) patients in group A and 7(22.5%) in group B (p=0.08). Plate breakage was noted in 3(9.6%) patients and screw breakage in 2(6.4%) patients in group B and none in group A (p=0.0001). Conclusion: Long working length titanium locking plates were found to be better than short working length in achieving fracture union and avoiding implant failure. Clinical Trial Number: ACTRN12619001023145 http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=377657&isReview=true Key Words: Bone plate, Bony callus, Femoral fractures, Fracture healings, Internal fixation device, Titanium.